The Future of Artificial Intelligence in 2D Game Development - Ahmad Fadhil Naswir (Journal of Data Science, Technology, and Computer Science, 2024)
The incorporation of Artificial Intelligence (AI) in game development has greatly transformed how games are created, designed, and experienced. Although AI's involvement in 3D games has been thoroughly examined, its use in 2D game creation offers distinct opportunities and challenges. This paper offers an extensive literature review on AI applications in 2D game development, addressing main topics like procedural content creation, adversary behavior, animation improvement, and player experience customization. This review examines recent research and case studies, emphasizing how AI-driven methods are transforming level design, enhancing the adaptability of non-player characters (NPCs), and optimizing the animation process. Nevertheless, in spite of these progressions, 2D game creators encounter difficulties like performance limitations, ethical issues, and the need to harmonize AI automation with human ingenuity. As AI technologies advance, upcoming innovations are anticipated to bring forth more advanced procedural generation methods, adaptive AI-enhanced gameplay, and highly personalized player experiences. This research seeks to close the knowledge gap in AI-powered 2D game development, providing insights into its existing applications and pinpointing research deficiencies that may inspire future advancements in the sector.